If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(5 + -4x) + 3 = -3(2x + 3) + -10x 3x + (5 * 2 + -4x * 2) + 3 = -3(2x + 3) + -10x 3x + (10 + -8x) + 3 = -3(2x + 3) + -10x Reorder the terms: 10 + 3 + 3x + -8x = -3(2x + 3) + -10x Combine like terms: 10 + 3 = 13 13 + 3x + -8x = -3(2x + 3) + -10x Combine like terms: 3x + -8x = -5x 13 + -5x = -3(2x + 3) + -10x Reorder the terms: 13 + -5x = -3(3 + 2x) + -10x 13 + -5x = (3 * -3 + 2x * -3) + -10x 13 + -5x = (-9 + -6x) + -10x Combine like terms: -6x + -10x = -16x 13 + -5x = -9 + -16x Solving 13 + -5x = -9 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 13 + -5x + 16x = -9 + -16x + 16x Combine like terms: -5x + 16x = 11x 13 + 11x = -9 + -16x + 16x Combine like terms: -16x + 16x = 0 13 + 11x = -9 + 0 13 + 11x = -9 Add '-13' to each side of the equation. 13 + -13 + 11x = -9 + -13 Combine like terms: 13 + -13 = 0 0 + 11x = -9 + -13 11x = -9 + -13 Combine like terms: -9 + -13 = -22 11x = -22 Divide each side by '11'. x = -2 Simplifying x = -2
| x(2)=49 | | 13m=12m-21 | | x*2*x^3*x^5= | | (2z+6)(2z-6)z= | | 13/11y-2/11y=-3 | | -2(b-4)=2b+8 | | -5(7x-12)+2(-6-10x)=-10x+3x | | (-2y^2)(4y)= | | z^2+3=4z | | -15x-1/3= | | z^2+3=3z | | q^2+19=20q | | 6x-3=4x+13 | | k/5.2+81.9=47.2 | | 14.5+x=6.2 | | x+15=-34 | | 4x^2-7=71 | | 2a^-1+3b^-2/a^-1-b^-1 | | x^4+14x^2+49= | | x^4-14x^2+49= | | (9x+7)(4x^2+5x+8)= | | -11(8p+4)=-11(p+11) | | -3x+2(-4)=10 | | 35p^6q^3/49p^6q^2 | | X+1/3x=36 | | 30/14=m/1.54 | | x^2+2x=26.01 | | 4(3x-4)=2(x-2) | | 9x-4=2(x+3) | | 3(5x-6)=-48 | | 4/3v-4/3 | | 26x+144x=0 |